2018
DOI: 10.3386/w24314
|View full text |Cite
|
Sign up to set email alerts
|

The Light and the Heat: Productivity Co-benefits of Energy-saving Technology

Abstract: Measurement of the full costs and benefits of energy-saving technologies is often difficult, confounding adoption decisions. We study consequences of the adoption of energy-efficient LED lighting in garment factories around Bangalore, India. We combine daily production line-level data with weather data and estimate a negative, nonlinear productivity-temperature gradient. We find that LED lighting, which emits less heat than conventional bulbs, decreases the temperature on factory floors, and thus raises produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 37 publications
(48 reference statements)
1
48
0
1
Order By: Relevance
“…Given that TFP is a weighted average of labor and capital productivity, we now turn to exploring whether these negative effects primarily originate from labor productivity, capital productivity, or both. Previous studies have predominantly focused on labor productivity (e.g., see Adhvaryu et al (2014); Somanathan et al (2014)). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that TFP is a weighted average of labor and capital productivity, we now turn to exploring whether these negative effects primarily originate from labor productivity, capital productivity, or both. Previous studies have predominantly focused on labor productivity (e.g., see Adhvaryu et al (2014); Somanathan et al (2014)). …”
Section: Resultsmentioning
confidence: 99%
“…This paper adds to recent firm-level studies (Adhvaryu et al, 2014;Somanathan et al, 2014;Chen and Yang, 2017) along with subnational (Colmer, 2017) and national-level (Hsiang, 2010;Dell et al, 2012;Burke et al, 2015) studies that have examined temperature effects on manufacturing activity around the world. In particular, consistent with Hsiang (2010) and Dell et al (2012)'s evidence from other parts of the world, we find that a 1 • F shift in the annual distribution of daily temperature reduces China's GDP by 0.92% through manufacturing sector impacts alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of impacts for the adoption of individual appliances appears challenging and very few studies have attempted to investigate it. Barreca, et al (2016) find that air conditioning lowered heat-related mortality in the US and there is a strong emerging evidence of the link between temperature and economic activity (Burke et al 2015, Adhvaryu et al 2016) which highlights the scope for adaptation strategies to climate change. Few studies assess the potential impact of refrigerators on food security and health.…”
Section: Electricitymentioning
confidence: 99%
“…Each additional degree Celsius (within the range of temperatures from 22 to 29°C) implies a reduction of 1.8% in labor productivity. Somanathan, Somanathan, Sudarshan, and Tewari () and Adhvaryu, Kala, and Nyshadham () showed that manufacturing workers' productivity at the plant level declines with hot days (a 1°C increase, above 25°C, causes a 2.8% reduction in plant‐level productivity) . Interestingly, these two studies disentangle the contributions of workers' productivity decline and workers' absenteeism.…”
Section: Introductionmentioning
confidence: 99%